1990
DOI: 10.1901/jeab.1990.53-5
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Effects of Smoked Marijuana: Behavioral Contingencies and Low‐probability Activities

Abstract: Six adult male research volunteers, in two groups of 3 subjects each, lived in a residential laboratory for 15 days. All contact with the experimenters was through a networked computer system, and subjects' behavior was monitored continuously and recorded. During the first part of each day, they were allowed to socialize. Two cigarettes containing active marijuana (2.7% delta 9-THC) or placebo were smoked during the private work period and the period of access to social activities. Three-day contingency condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
(23 reference statements)
2
13
0
Order By: Relevance
“…Hence, consistent with the increased breakpoints observed for THC in previous food-reinforced PR studies in rats (Higgs et al 2005; Solinas and Goldberg 2005; Wakley and Rasmussen 2009), the present results also do not support a generalized decrement in motivation for food reward following THC administration. Rather, they are consistent with laboratory studies in humans that have failed to find a THC-induced amotivational effect (Foltin et al 1990; Foltin et al 1989b). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hence, consistent with the increased breakpoints observed for THC in previous food-reinforced PR studies in rats (Higgs et al 2005; Solinas and Goldberg 2005; Wakley and Rasmussen 2009), the present results also do not support a generalized decrement in motivation for food reward following THC administration. Rather, they are consistent with laboratory studies in humans that have failed to find a THC-induced amotivational effect (Foltin et al 1990; Foltin et al 1989b). …”
Section: Discussionsupporting
confidence: 88%
“…This pattern of behavior was observed to be most severe for people who had been using marijuana the longest, and ceased when the individuals discontinued marijuana use (Maugh 1974). While amotivational syndrome has been observed clinically, laboratory research with humans has not shown evidence for marijuana-induced amotivational syndrome in regular users of marijuana (Foltin et al 1990; Foltin et al 1989a). Occasional users of marijuana, however, show decreased motivation in a task reinforced by money at low pay rates, but not at higher pay rates (Cherek et al 2002), suggesting that nonpharmacological factors may modulate marijuana’s effects on motivation.…”
mentioning
confidence: 99%
“…The right inferior and middle frontal gyri are involved in risk attitudes and contingency awareness (Carter et al, 2006). These behaviors are affected by THC (Foltin et al, 1990), but are much dependent on the exact type of behavior that is tested (McDonald et al, 2003;Zuurman et al, 2009). One FMRI-study, for example, showed that THC attenuated activity in the right inferior frontal and anterior cingulate gyri when performing the Go/No-Go task for response inhibition, but no difference was seen on the task performance itself (Borgwardt et al, 2008).…”
Section: Noimentioning
confidence: 99%
“…Previous research had established as well that the performance battery required only a brief amount of time to complete and was sensitive to manipulations, such as drug administration and changes in nutrition, known to affect human behavior (e.g., Foltin et al, 1990;Kelly, Foltin, & Fischman, 1993;Kelly, Foltin, Rolls, & Fischman, 1994;Kelly, Foltin, Serpick, & Fischman, 1997;Ward, Kelly, Foltin, & Fischman, 1997). During each test session, the tasks were presented in the following order:…”
Section: Task Batterymentioning
confidence: 99%